Analisis Lokasi dan Pola Sebaran Pasar Modern di Kota Yogyakarta, Kabupaten Sleman dan Bantul - Wahyuningsih, Tri; Harmadi, Sonny Harry B (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
The development of modern market which is penetrated into the rural areas has positive impactson fast distribution of goods and price stability in that region. However, people are afraid thatthe change of city spatial functions will bring more harm to the existence of a traditional marketor a small retailer that is the source of living for lower-middle income group. This studyidentifies some factors influencing the number of modern market in Yogyakarta city, Selmanand Bantul regencies by considering the spatial interaction pattern among districts. The resultsshow that the location of modern market is influenced by population density and quality of roadinfrastructure. There is a spatial dependence among the location of modern markets in a form ofspatial error model. The identification of spatial error is believed that there are several variableswhich are not included in the model but has an important role spatially, namely the price of landand local government policy.